Intercultural education in spanish shools - Henar Rodríguez Navarro; Beatriz Gallego López; Clara Sansó Galiay; José Luis Navarro Sierra; Marta Velicias Sánchez; Mónica Lago (Revista Electrónica Interuniversitaria de Formación del Profesorado)
There are many initiatives about intercultural education in our country. This work focuses on highlighting intercultural teaching practices that have been done in Spain in recent decades. Firstly, Spanish educational policies are presented; then some teaching practices are described. The analysis has been divided into seven areas: I.- Welcome Plans; II.- Linguistic and Cultural Attention; III.- Cooperative Management Strategies in classrooms; IV.- Community Implication; V.-Intercultural Mediation and resolution of conflicts ; VI.- Teachers´ training and VII.- Observatories of several communities. We could analyze these topics from two points of view: one related to inclusive education and, on the other hand, the related to compensatory education. Finally, intercultural practices and learning Communities experiences are connected, considering that both could give an answer to intercultural practices described before. This article presents part of a research project carried out by the group ACOGE of the University of Valladolid.